A survey of Catholic secondary school libraries in Oriental Mindoro a preliminary step in accreditation - Manguiat, Juanita M. (1978)
This is a survey of thirteen catholic secondary school libraries in Oriental Mindoro during the school year 1977-1978 in order to present comprehensive information about the library services and facilities in relation to accreditation standards.